2010
DOI: 10.1007/s10482-010-9467-8
|View full text |Cite
|
Sign up to set email alerts
|

Aurifilum, a new fungal genus in the Cryphonectriaceae from Terminalia species in Cameroon

Abstract: Native Terminalia spp. in West Africa provide a popular source of construction timber as well as medical, spiritual and social benefits to rural populations. Very little is, however, known regarding the diseases that affect these trees. During an investigation into possible diseases of Terminalia spp. in Cameroon, orange to yellow fungal fruiting structures, resembling those of fungi in the Cryphonectriaceae, were commonly observed on the bark of native Terminalia ivorensis, and on dead branches of non-native … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…Research showed that some pathogens in the Cryphonectriaceae may undergo host shifts (Slippers et al 2005), enabling them to infect tree species other than their native hosts (Wingfield 2003;Gryzenhout et al 2004Gryzenhout et al , 2006bGryzenhout et al , 2009Gryzenhout et al , 2010Heath et al 2006;Nakabonge et al 2006a, b;Begoude et al 2010;Vermeulen et al 2011). It has been suggested further that species of Chrysoporthe that infect non-native plantation-grown Eucalyptus have originated from native trees in the Myrtales Rodas et al 2005;Heath et al 2006;Gryzenhout et al 2006bGryzenhout et al , 2009Gryzenhout et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research showed that some pathogens in the Cryphonectriaceae may undergo host shifts (Slippers et al 2005), enabling them to infect tree species other than their native hosts (Wingfield 2003;Gryzenhout et al 2004Gryzenhout et al , 2006bGryzenhout et al , 2009Gryzenhout et al , 2010Heath et al 2006;Nakabonge et al 2006a, b;Begoude et al 2010;Vermeulen et al 2011). It has been suggested further that species of Chrysoporthe that infect non-native plantation-grown Eucalyptus have originated from native trees in the Myrtales Rodas et al 2005;Heath et al 2006;Gryzenhout et al 2006bGryzenhout et al , 2009Gryzenhout et al , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…These were supplemented by analyses of the conserved 5.8S rDNA and the exon regions of the BT (including partial exon 4, exon 5, partial exon 6 and partial exon 7) gene regions for previously described species in the Cryphonectriaceae (Gryzenhout et al 2009, Begoude et al 2010, Vermeulen et al 2011). The datasets of Gryzenhout et al (2006aGryzenhout et al ( , 2009 (Gryzenhout et al 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cryphonectriaceae includes fungi previously treated broadly in the Cryphonectria-Endothia complex (Gryzenhout et al 2009) and currently accommodates 12 genera (Gryzenhout et al 2009(Gryzenhout et al , 2010aBegoude et al 2010;Chungu et al 2010). The family includes important tree pathogens, such as Chrysoporthe austroafricana Gryzenh.…”
Section: Introductionmentioning
confidence: 99%